THE THEORETICAL UNDERPINNINGS OF THE SOLID WASTE MANAGEMENT PRACTICES: A PROPOSED BLUEPRINT TOWARDS GOVERNMENT ACTION - Lagbas - Aranas, Amelia Girly U. (European Scientific Journal, ESJ, 2015)
This research paper theoretically underpins the solid waste management practices in the Pacific Area of Southern Leyte as basis for a proposed blueprint towards government action that will serve as an addendum of the existing programs in accordance with the mandate under R.A. 9003 for an enhanced and intensified initiative of the local government unit(s) to address waste problems in cooperation with other concerned stakeholders (private sectors and non-government organizations) of the society.